A DESCONCENTRAÇÃO INDUSTRIAL NO ESTADO DE SÃO PAULO E A EXPANSÃO DO COMÉRCIO E DO SETOR DE SERVIÇOS - Cleps, Geisa Daise Gumiero (Caminhos de Geografia, 2003)
This research try to look for the process of industrial disconcentration occurred in São Paulo state, since 1970, and the trade and service sector development. It brings a raise of the key factors that causes the interiorization of industrial activities in this state and another brazilian regions. According to economic development accepted for the coutry and their awn disconcentration of industrial activity, this work still search to discuss the trade and service and service sector discincentration.